Instructional models for physical education - Metzler, Michael; Colquitt, Gavin (New York Oxon Routledge, 2021)
No single instructional method can meet all of the student learning needs expressed in the SHAPE American National Standard for Physical Education. This new edition provides pedagogical knowledge and resources that support physical education teachers' selection and use of instructional models and gives physical educators a plan for incorporating these models into teaching. Presented in two sections, Instructional Models for Physical Education 4E first presents the rationale, pedagogical knowledge, and selection processes for Model-Based Instruction (MBI). MBI is the commitment to use one instructional plan throughout a unit of instruction. The second section provides pedagogical knowledge for the selection, implementation, and assessment of instructional models used in P-12 physical education. This edition has been updated to be in alignment with the SHAPE America National Standards for Physical Education. It includes new sections on differentiated instruction and practical applications. A companion website contains additional examples and information for each model. The book includes everything the reader needs for planning, implementing, and assessing when teaching with instructional models. It helps readers incorporate research-based practices in their lessons, adapt activities, and teach to standards. This text can be used as the stand-alone text for courses on physical education teaching methods at the undergraduate and graduate levels
1. Aligning standards, curriculum, and instruction with model-based instruction -- 2. Describing instructional models for physical education -- 3. Areas of knowledge for mode-based instruction and physical education -- 4. Teaching strategies for model-based instruction -- 5. Effective strategies for model-based instruction -- 6. Planning for model-based instruction -- 7. Assessing student learning in model-based instruction -- 8. Direct instruction -- 9. Personalized system for instruction -- 10. Cooperative learning -- 11. Sport education -- 12. Peer teaching -- 13. Inquiry teaching -- 14.Tactical games -- 15. Teaching personal and social responsibility
Includes bibliographical references and index
Keywords: Physical education and training -- Study and teaching -- United States; Physical education teachers -- Training of -- United States